THE NECESSARY AND SUFFICIENT CONDITION FOR THE δ - POROSITY OF THE CONVERGENCE FIELD OF REGULAR MATRIX TRANSFORMATIONS - NKUNO, DAUDA INUWA; KILTHO, AHMADU; NWUNUJI, ADAMU A. (My University, 2025)
It has been shown by some researchers that the convergence field of regular matrix transformation is a very porous set in the spaceof all sequence of real or complex numbers while in [3], it have been proven to be σ-porous set in the linear metric space endowed with Fréchet metric. Also, the usefulness of the well-known theorem on discontinuity points of function of the first bare class has been presented. Thus in this paper, we provided the necessary and sufficient conditions under which the convergence field of a various matrix transformation is σ-porous.
Jobless Ph. D. Student
Keywords: Porosity; σ-porous; Regular matrix; matrix transformation; convergence field